Prioritizing Critical Success Factors of Requirements Engineering using Analytical Hierarchy Process - Imairi Eitiveni; Hardyn Alexander Hutapea (Jurnal Sistem Informasi, 2023)
Requirements engineering is not as straightforward as asking stakeholders what they want the information systems to do. In most cases, their vision tends to be limited by the status quo. Eliciting a complete set of requirements that fulfil every gap and withstand scrutiny during validation is challenging. Hence, it is important to consider various factors influencing the success of requirements engineering. This paper identifies and prioritizes multiple critical success factors of requirements engineering using the Analytical Hierarchy Process. The initial model was developed from literature review and validated using evidence from an empirical study. Quantitative data was collected through a questionnaire and then analyzed to rank the success criteria and critical success factors. The results show that the user satisfaction is the most important success criterion, while the clear definition of project scopes and goals is the most critical factor for the success of requirements engineering.